A Rare Congenital Splenic Fissure: Insights from a Cadaveric Study (AYUSHDHARA, 2025)
The spleen, an important organ of the immune and circulatory systems, lies in the left hypochondriac region between the 9th and 11th ribs. It develops from the mesoderm as distinct lobules, which later fuse. In adults, residual notches along the superior border indicate this early lobulated stage. Congenital anomalies such as persistent lobulation, accessory spleens, and polysplenia are generally asymptomatic. Case Findings: During routine cadaveric dissection, a rare anatomical variation was observed- a sharp fissure measuring approximately 2cm in depth along the superior border. This fissure separated a distinct lobule on the diaphragmatic surface extending to the visceral surface. Such deep clefts occur in about 10% of individuals, but this presentation was unusually well- defined. Diagnosis and Management: The fissure was identified as a possible congenital anomaly, with no clinical symptoms and no intervention required. Clinical Significance: Knowledge of splenic morphology, including variations in notches and fissures, is essential for accurate diagnosis and surgical planning. Persistent fissures may be mistaken for traumatic lacerations or pathological lesions on imaging. This case highlights the importance of recognising rare congenital variations to avoid diagnostic errors and ensure safe clinical management.